PENGARUH NILAI PELANGGAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMILIHAN PENDIDIKAN KAMPUS BERBASIS VOKASI - Minggu Minggu; May Vitha Rahmadhani; Siswandi Siswandi (POLITEKNIK LP3I JAKARTA, 2020)
This research was conducted to determine how much the influence Customer Value to the College Selection Decision of Student in Polytechnic LP3I Jakarta Kampus Blok M, to determine how much the influence Quality 0f Education Services to the College Selection Decision of Student in Politectic LP3I Jakarta Kampus Blok M, and determine how much the influence Customer Value and Quality of Education services simultaneously to the College Selection Decision of Student in Polytechnic LP3I Jakarta Kampus Blok M. This research was conducted on 75 students out of a population of 300 students using slovin method and quantitative research methods using regression analysis, to prove that the variable customer value has a positive and significant influence towards college selection decisions; and the variable quality of educational services has a positive and significant influence towards college selection decision. The research proved that the customer value has a positif influence 0,823 to the college selection decision,the quality of educational services has a positif influence 0,756 to the college selection decision,customer value and quality of education services simultaneosly has a significant influence 0,854. The Results of this research prove that hypotests Ha accepted and proven linear.Keywords: College Selection Decision, Customer Value, Service Quality